Development of a high‐throughput real‐time PCR assay for the detection of the R81T mutation in the nicotinic acetylcholine receptor of neonicotinoid‐resistant Myzus persicae. Issue 2 (23rd April 2012) - Puinean, Alin M; Elias, Jan; Slater, Russell; Warren, Anne; Field, Linda M; Williamson, Martin S; Bass, Chris
Abstract BACKGROUND: Myzus persicae is a globally important aphid pest that is mainly controlled through the application of chemical insecticides. Recently, a clone of M. persicae exhibiting control‐compromising levels of resistance to neonicotinoid insecticides was described. The resistance of this clone was associated with reduced affinity of imidacloprid for the target site (the nicotinic acetylcholine receptor) as a result of mutation of a key amino acid residue (R81T) in the loop D region of a nAChR β1 subunit. The potent levels of resistance conferred by this mechanism are cause for considerable concern, and the frequency and distribution of the mutation in worldwide populations of M. persicae require careful monitoring. In this study, a high‐throughput assay has been developed that allows detection of the mutation in individual aphids. RESULTS: A real‐time TaqMan assay to detect the R81T substitution was developed that proved to be sensitive and specific in tests of analytical sensitivity and in a blind genotyping trial of DNA extracted from individual aphids comprising the three possible genotypes. The assay was then used to examine the frequency of the R81T mutation in aphids collected and stored in ethanol from peach orchards in southern France. The R81T frequency varied from 33 to 100% in seven populations from the department of Gard, France. CONCLUSIONS: This study describes a rapid and sensitive assay that very effectively detects the R81T mutation in individual aphids. The results also have practical significance for the control of M. persicae in southern France and provide contemporary data to inform current resistance management strategies. Copyright © 2012 Society of Chemical Industry